Enterprise interactions: conceptualisation, ontology, and standard architectures and services. (2018) - Baghdadi, Youcef
Enterprise interactions involve different types of autonomous, heterogeneous, and loosely coupled actors, which requires integration architectures that enable flexibility and agility. This paper proposes a framework to conceptualise the enterprise interactions, geared toward a lightweight ontology. This ontology is meant to understand the semantics of the different types of enterprise interactions, in order to rationally decide the required standard architectures and services that facilitate the integration with the current (or to develop) technologies such as extended social websites, Internet of Things (IoT), web services and micro-services-based service oriented architecture (SOA), and cloud computing.